The Influence Of Company Size, Audit Delay, And Audit Rotation On Audit Quality (Empirical Study On Consumer Goods Industry Sector Companies Listed On The IDX 2020-2022) - Amanda, Ni Nyoman Ayu Natasya; Suryanawa, I Ketut (Jurnal Ekonomi, 2024)
Company size, audit delay, and audit rotation are the variables that this research intends to examine in relation to audit quality. firms listed on the IDX that publish full audited financial reports from the consumer goods industry between 2020 and 2022 (BEI firms) provided the data used in this study. Based on purposive sampling approaches, a total of 189 observations were utilized for the samples. The data was analyzed using SPSS 26 and logistic regression. The results indicate that firm size has a positive effect on audit quality, audit delay has a negative effect on audit quality, and audit rotation has no effect on audit quality.